ISOTOPICALLY LIGHT METHANE IN NATURAL GAS: BACTERIAL IMPRINT OR DIFFUSIVE FRACTIONATION? - Prinzhofer A.; Pernaton E. (My University, 1997)
The evaluation of the economic importance of bacterial methane is still a matter of discussion, linked to the evolution of the geochemical understanding. Methane occurrence or accumulations with light isotopic ratios, both for carbon and hydrogen, were thought in earlier days to be primarily due to migration. Then, from several works presented in the eighties, it was claimed that (a) bacterial methane had the same light isotopic signatures as those found in some gas accumulations, mainly at shallow depths, where bacterial activity is possible, and that (b) migration could not induce measurable isotopic fractionation. This gave a non ambiguous origin (bacterial occurrence) for any gas having 12C-enriched methane. Looking back at the experimental and physical evidence of this last assessment, and taking into account the consequences of some new series of gas migration experiments, we now consider that both explanations for isotopically light methane (bacterial generation or migration fractionation) are realistic. Using a simple diagram (ethane over methane versus the carbon isotopic ratio of methane), and modelling the two discussed processes (mixing of bacterial and thermal gas, or diffusion of thermal gases), it is possible in several cases to decipher the origin of the gas series. It would appear for example that Italian gases correspond grossly to a simple mixture between bacterial and thermogenic gases, whereas other gases of various origins (head space gases, gases from German coals, shallow gas pockets in recent sediments, Mexican deep overmature gases) show a trend that we interpret as a result of diffusive fractionation.
Keywords: NATURAL GAS; CARBON ISOTOPES; MIXING; BACTERIAL METHANE; SEGREGATION; DIFFUSION